Sensores de campo magnético débil y su aplicación en magnetocardiografía - Rodríguez-Rodríguez, E.; Godínez-Fernández, R.; Barrales-Guadarrama, R.; Vázquez-Cerón, E. (Revista Mexicana de Ingenieria Biomedica, 2005)
In the last years, the Magnetocardiography has been increased as a complementary tool in traditional electrocardiography studies, with the purpose of increasing the precision in the diagnosis of heart pathologies. Magnetocardiography requires technology that only counts developed countries. In this work, we show the advance of the project whose objective is to apply technology and physical infrastructure in order to obtain magnetic heart signals. The critical part of the project is the development of the magnetic sensor that can sense weak magnetic field in order to detect heart magnetic activity using interferometric methods. In this sensor, the magnetic field is detected as a function of the interference that happens among the feeding currents and induced currents in the well-known sensor as SQUID (Superconductor Quantum Interference Device), that consist of two Josephson junction connected in parallel. Although some countries this technique is already used as complementary information of ECG, in Mexico not yet has been developed. We show fabrication and characterization of superconductor thin film like an advance to the construction of a SQUID sensor, in order to this we design and build an ablation system and we explore with a low-cost Cu substrate to obtain the thin film.